Dose-dependent transcriptomic responses of zebrafish eleutheroembryos to Bisphenol A. (December 2018) - Martínez, Rubén; Esteve-Codina, Anna; Herrero-Nogareda, Laia; Ortiz-Villanueva, Elena; Barata, Carlos; Tauler, Romà; Raldúa, Demetrio; Piña, Benjamin; Navarro-Martín, Laia
Abstract: Despite the abundant literature on the adverse effects of Bisphenol A (BPA) as endocrine disruptor, its toxicity mechanisms are still poorly understood. We present here a study of its effects on the zebrafish eleutheroembryo transcriptome at concentrations ranging from 0.1 to 4 mg L −1, this latter representing the lowest observed effect concentration (LOEC) found in our study at three different macroscopical endpoints (survival, hatching and swim bladder inflation). Multivariate data analysis methods identified both monotonic and bi-phasic patterns of dose-dependent responses. Functional analyses of genes affected by BPA exposure suggest an interaction of BPA with different signaling pathways, being the estrogenic and retinoid receptors two likely targets. In addition, we identified an apparently unrelated inhibitory effect on, among others, visual function genes. We interpret our data as the result of a sum of underlying, independent molecular mechanisms occurring simultaneously at the exposed animals, well below the macroscopic LOEC, but related to at least some of the observed morphological alterations, particularly in eye size and yolk sac resorption. Our data supports the idea that the physiological effects of BPA cannot be only explained by its rather weak interaction with the estrogen receptor, and that multivariate analyses are required to analyze the effects of toxicants like BPA, which interact with different cellular targets producing complex phenotypes. Graphical abstract: Image 1 Highlights: Bisphenol A (BPA) affects steroid, lipid, and visual pathways in zebrafish embryos. BPA induces persistence of yolk sac remains at 5 dpf and a reduction of eye size. Transcriptomic changes can be linked with the observed macroscopic alterations. Transcriptomic effects occur at 1/5 to 1/10 of the macroscopic LOEC. We propose an interaction of BPA with the estrogen and retinoid regulatory pathways. Abstract : Estrogenic- and retinoid-like transcriptomic effects of bisphenol A in zebrafish eleutheroembryos and their relationship with morphological alterations.